NUCLEOSYNTHESIS AT MAGNETOROTATIONAL SUPERNOVA EXPLOSION AND GALACTIC CHEMICAL EVOLUTION - Kondratyev, V. N.; Mishenina, T. V. (Одеські астрономічні публікації, 2016)
Synthesis of chemical elements is investigated at conditions of magnetorotational instabilities in astrophysical plasma at supernova explosion. Effects of ultra-strong nuclear magnetization are demonstrated to enhance the portion of titanium product. The relation to an excess of 44Ti revealed from the Integral mission data and galactic chemical evolution is discussed.